1979
DOI: 10.1136/gut.20.3.216
|View full text |Cite
|
Sign up to set email alerts
|

Amylase activity in human bile.

Abstract: SUMMARY The mean amylase level in 42 human bile samples was 154 IU/l and there was no significant difference in the amylase activity of 32 paired serum and bile samples. Estimation of the amylase thermolability of bile showed it to be similar to that of serum. This suggests that the amylase activity in bile may have filtered through the liver from the hepatic circulation rather than refluxed from the pancreatic duct. The presence of amylase in human bile provides further evidence that the liver might have a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 19 publications
(15 reference statements)
2
16
0
Order By: Relevance
“…There have been a few observations of the activity of pancreatic enzymes in the epithelial cells of nonpancreatic organs [1,[3][4][5] and some ultrastructural observations of zymogen granules in these cells [6,18]. However, we find the presence of pancreatic digestive enzymes in several nonpancreatic gastrointestinal organs, albeit at much lower levels than in the pancreas, confirming that the nonpancreatic organs produce much smaller quantities of pancreatic digestive enzymes than does the pancreas.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…There have been a few observations of the activity of pancreatic enzymes in the epithelial cells of nonpancreatic organs [1,[3][4][5] and some ultrastructural observations of zymogen granules in these cells [6,18]. However, we find the presence of pancreatic digestive enzymes in several nonpancreatic gastrointestinal organs, albeit at much lower levels than in the pancreas, confirming that the nonpancreatic organs produce much smaller quantities of pancreatic digestive enzymes than does the pancreas.…”
Section: Discussionsupporting
confidence: 84%
“…Although lipase activity has been noted in several tissues, including the stomach (gastric lipase) [1,3,16,17,25,34], pancreatic lipase has not been reported in non-pancreatic organs. Donaldson et al [5] reported amylase activity in the human bile, and recently Doglioni et al [4] reported that pancreatic acinar metaplasia in the stomach was positive for immunoreactive pancreatic α-amylase and lipase. There have been no systematic reports on the in situ expression of pancreatic digestive enzymes in nonpancreatic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Pervious reports have considered various levels of amylase in bile, to be normal (e.g., <1000 3 and <10 000 11 IU/l). Donaldson et al 12 carried out intraoperative sampling of bile in patients without liver disease whose serum hepatobiliary enzyme levels were normal, and analysis of the bile revealed no difference between the amylase level in bile and the serum amylase level. Sai et al 3 also reported that the biliary amylase level (238 IU/l) in patients without refl ux of pancreatic juice into the bile duct on MRCP was no different from the serum amylase level (130-400 IU/l).…”
Section: Discussionmentioning
confidence: 98%
“…Regurgitation of pancreatic juice into the bile duct was observed in 5.4% of patients with a morphologically normal pancreaticobiliary ductal arrangement regardless of the length of the common channel, and that patient group showed a higher amylase level in bile and a higher prevalence of gallbladder cancer compared with those without such regurgitation. The origin of amylase in bile is thought to be serum amylase that has passed through the liver as well as refl ux from the pancreatic duct, 12 and no consensus has been reached regarding the normal level of amylase in bile. In this particular study, only patients whose serum amylase level was normal were included.…”
Section: Discussionmentioning
confidence: 99%
“…The origin of amylase in bile is thought to be serum amylase that has passed through the liver, as well as reflux from the pancreatic duct [16], and no consensus has been reached regarding the normal level of amylase in bile. Several studies have reported that there is no difference between the biliary amylase level in the gallbladder and the serum amylase level in patients without liver disease or pancreaticobiliary maljunction [10,16].…”
Section: Discussionmentioning
confidence: 99%